2010
DOI: 10.1111/j.1745-4557.2010.00346.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF DRIED MORINGA (MORINGA OLEIFERA LAM) LEAVES ON RHEOLOGICAL, MICROSTRUCTURAL, NUTRITIONAL, TEXTURAL AND ORGANOLEPTIC CHARACTERISTICS OF COOKIES

Abstract: Effect of replacement of wheat flour with 5, 10 and 15% dried moringa leaves (Moringa oleifera Lam) powder (DML) on the rheological, microstructural, nutritional and quality characteristics of cookies was studied. Incorporation of increasing amount of DML from 0 to 15% increased farinograph water absorption and decreased dough stability, amylograph pasting temperature and peak viscosity. Use of DML increased dough hardness and decreased cohesiveness and spread ratio of cookies. Sensory evaluation showed that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
101
2
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(142 citation statements)
references
References 15 publications
33
101
2
6
Order By: Relevance
“…The decrease in peak viscosity may be due to the partial gelatinisation of starch and denaturation of proteins and less water available for initial swelling of starch granule (Yadav et al 2008;Symons and Brennan 2004). Earlier also Dachana et al (2010) reported decrease in peak viscosity with the increase in dried moringa leaves. The break down which is highly influenced by the amylose content and a measure of susceptibility of cooked starch granules to disintegration decreased significantly (p ≤0.05) from 54.50 to 47.10 RVU.…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…The decrease in peak viscosity may be due to the partial gelatinisation of starch and denaturation of proteins and less water available for initial swelling of starch granule (Yadav et al 2008;Symons and Brennan 2004). Earlier also Dachana et al (2010) reported decrease in peak viscosity with the increase in dried moringa leaves. The break down which is highly influenced by the amylose content and a measure of susceptibility of cooked starch granules to disintegration decreased significantly (p ≤0.05) from 54.50 to 47.10 RVU.…”
Section: Resultsmentioning
confidence: 80%
“…The increase in water absorption may be attributed to the fact that hydroxyl groups present in the fibre structure allow more water interaction through hydrogen bonding. Earlier, Dachana et al (2010) and Gomez et al (2003) also reported addition of fiber increase water absorption in cookies and bread due to the hydroxyl groups present in the fiber. The time required for dough development or to reach a dough consistency equivalent to 2,200 mb pressure (Tpr) was increased from 110 to 260 s, whereas the tolerance (To1) which measures the stability of the dough, decreased with the increase in the concentration of spinach powder from 301 to 165 s. The increase in time for dough development and decrease in stability may be attributed to the decrease in the strength of dough due to increase in fiber content owning to dilution and disruption of continuity of gluten.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations